2022
DOI: 10.3390/diagnostics12102519
|View full text |Cite
|
Sign up to set email alerts
|

Acanthosis Nigricans: Pointer of Endocrine Entities

Abstract: Acanthosis nigricans (AN) has been reported in relation to insulin resistance (IR). We aim to review AN through an endocrine and metabolic perspective focusing on IR in association with metabolic complications such as obesity, diabetes mellitus (DM), and metabolic syndrome (MS) with/without polycystic ovary syndrome (PCOS). We revised English papers on PubMed covering publications from the last 5 years. The current prevalence of AN varies from 4.5 to 74% (or even 100%, depending on the studied population), wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 189 publications
0
4
0
Order By: Relevance
“…The multiple regression showed a significant influence of the blood parameters investigating IR (HOMA-IR, fasting glucose, VAI, and TyG index) on serum TMAO, but only HOMA-IR and fasting glucose were confirmed as independent predictors of TMAO. Moreover, when investigating the presence of acanthosis nigricans as a marker of insulin resistance ( 62 ), this study showed that an increase in TMAO is associated with an increase in the probability of the presence of acanthosis nigricans. Insulin resistance itself is an aggravating factor for the progression of vascular disruptions in obese children ( 137 ).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The multiple regression showed a significant influence of the blood parameters investigating IR (HOMA-IR, fasting glucose, VAI, and TyG index) on serum TMAO, but only HOMA-IR and fasting glucose were confirmed as independent predictors of TMAO. Moreover, when investigating the presence of acanthosis nigricans as a marker of insulin resistance ( 62 ), this study showed that an increase in TMAO is associated with an increase in the probability of the presence of acanthosis nigricans. Insulin resistance itself is an aggravating factor for the progression of vascular disruptions in obese children ( 137 ).…”
Section: Discussionmentioning
confidence: 87%
“…Tanner stages were determined for each participant (Tanner 1 represents pre-puberty; Tanner 2-4 represents puberty; Tanner 5 represents post-puberty) ( 61 ). The presence of acanthosis nigricans was noted ( 62 ). Post-pubertal girls were asked whether they had regular or irregular menses.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, the study had limitations, including a relatively small sample size and a short follow-up period, which may limit the generalizability of the results. Additionally, the occurrence of adverse effects like pruritus and redness in the TCA group and burning and skin peeling in the Tretinoin group highlight the importance of considering patient tolerance and comfort in treatment selection (21).…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis, in most cases, should be limited to dermatoscopy; however, in some cases, a biopsy may be indicated to differentiate dark acanthosis from other discolorations. [2] [8] [17] Hidradenitis suppurativa (inverse acne) is a chronic inflammatory skin disease that begins in hair follicles and, in collaboration with bacterial infection, leads to the formation of painful inflammatory nodules, abscesses, and skin fistulas. It is most commonly located in areas where the skin rubs against itself, such as the underarms, breasts, and groin, but as the disease progresses, it can affect body regions such as the neck, limbs, or skin behind the ears.…”
Section: Skin Diseases Co-occurring With Diabetesmentioning
confidence: 99%